Optimalisasi Sumberdaya Sungai : Dampaknya Bagi Pembangunan Industri dan Sektor Pertanian - Teguh Kismantoroadji (Jurnal Dinamika Sosial Ekonomi, 2002)
Rivers have strategic function in suppling of water need on toun and rural areas. The various socio-economics and biophysic zone therefore regional approach, which is integrated with area agroecosystem condition to increase efficiency in compiling the integrated agricultural strategic, with interest the area potential of resource and comparative advantage. The optimation of river endeavor, include to prevent bad side effet, failed. The main problems come from some sustainable violator should be pioneering. key words : natural resource, regional, agroecosystem, industry, agriculture